The economic value of improved wastewater irrigation: a contingent valuation study in Addis Ababa, Ethiopia - Weldesilassie, A.B.; Fror, O.; Boelee, Eline; Dabbert, S. (2009)
In developing countries the use of wastewater for irrigation can cause considerable harm to public health and the environment. This paper uses contingent valuation to estimate the economic value of safe use of wastewater for crop production on farms within and around Addis Ababa, Ethiopia. We estimate a surprisingly large welfare gain from policies for safe use of wastewater for irrigation. Our study highlights the potential and the possible pitfalls of using nonmarket valuation techniques as an input into public decision making where traditional resource use interacts with public health and environmental concerns in complex ways.